Histogram of edge-contour for ARIID fish images / Mohammad Ariff Md Yusof - Md Yusof, Mohammad Ariff (2009)
Manual system to retrieve information about lots of images is hard and cumbersome. The information has to be extracted from books, journals, or any other printed or electronic media. Nowadays, image retrieval can be found in the form of complex system but at the same time making it easier to match images with other images when queried. This study is focused on extracting edges from images of fishes. It can be used to match and identify which family or species the fish came from and retrieve other images of fish of the same family in an image retrieval system which can be developed by enhancing this image processing system.